Generalized trust and organized group membership among young Australians - Chong, Sheau Tsuey; Mohamad, Mohd Suhaimi; Mohd Hoesni, Suzana; Mohamad, Lukman @ Zawawi; Ibrahim, Fauziah; Sarnon @ Kusenin, Norulhuda; Nen, Salina; Subhi, Nasrudin; Jusoff, Kamaruzaman; Alavi, Khadijah; Abdul Kadir, Aeslina (IDOSI Publications, 2011)
Organized group membership has been central in discussions of social capital since generalized trust is believed to be generated through continuous interaction in social relationships. Is this mechanism for social capital generation affected by different levels of involvement by individuals in organized groups? The focus of this paper is to investigate whether active membership makes a difference to individuals' levels of generalized trust. Young Australians and permanent residents aged 16 to 25 (N=283) participated in this study through an online survey. The findings showed that members of organized groups were more trusting than those who do not participate in any group. The results also indicate that active members were relatively more trusting, as were those who participated in hobby groups. Furthermore, members of organized groups that were organized by community organizers accommodate more trusting people. However, the number of memberships one holds does not affect one's level of generalized trust.